Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.129
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Infestation in the Incidence of Diarrhea Among Toddlers in Jakarta, Bogor, Banjarmasin and Makassar

Abstract: The occurrence of diarrhea in children under five years old (toddlers) is still a serious health problem because it can cause mortality and malnutrition in children. Diarrhea is one of the biggest causes of death in toddlers in the world. Data from the World Health Organization (WHO) reports that more than 10 million children under five years old die every year and around 20 percent of them die because of diarrhea. One etiology of diarrhea infection in children under five years old who often escapes attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The study showed that the E. histolytica was considerably more prevalent in the age group <1-3 years (62.9%) and lower in the age group 10-12 years(3.8%), this variation was high significant (P = <0.0001),as summaries in (Table 5). The results of the present study was agree with Ahmed's study 2016(4) which found higher rate of infection in age group (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months and (25-36)months after examined 185 diarrheal children. Mathurin and his team (20)which reported that the age group 0-24 months and 5-36 months showed high rate of E. histolytica infection while, fewer infections were detected in the older children.…”
Section: Distribution Of the Patients According To The Age Groupssupporting
confidence: 92%
See 2 more Smart Citations
“…The study showed that the E. histolytica was considerably more prevalent in the age group <1-3 years (62.9%) and lower in the age group 10-12 years(3.8%), this variation was high significant (P = <0.0001),as summaries in (Table 5). The results of the present study was agree with Ahmed's study 2016(4) which found higher rate of infection in age group (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months and (25-36)months after examined 185 diarrheal children. Mathurin and his team (20)which reported that the age group 0-24 months and 5-36 months showed high rate of E. histolytica infection while, fewer infections were detected in the older children.…”
Section: Distribution Of the Patients According To The Age Groupssupporting
confidence: 92%
“…In another study conducted in Baghdad(31) they found that among 240 diarrheal children younger than5 years, 99 (41.25%) cases have E.histolytica. Kavili (17)clarified the prevalence of E. histolytica infections in 42.1% amongst the pupils ranged from 6 to 12 years old. In other hand, the results of the present study disagree with several previous studies.…”
Section: Detection Of Entamoeba Histolytica By Microscopic Examinationmentioning
confidence: 98%
See 1 more Smart Citation